Metallic Ratio Triads, The Mathematical Relations between different Metallic Means, And Geometric Substantiation of Metallic Numbers with the Right Angled Triangles (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
This paper synergize the newly discovered generalised geometry of all Metallic Means and the recently published mathematical formulae those provide the precise correlations between different Metallic Ratios. The paper also illustrates the concept of the “TRIADS of Metallic Means”.  The Metallic Means and their TRIADS can be geometrically substantiated, in an intriguing manner, as described in this paper.